Kinetic analysis of Copper(I)/Feringa-Phosphoramidite Catalysed AlEt3 1,4-Addition to Cyclohex-2-en-1-one - Willcox, Darren; Nouch, Ryan; Kingsbury, Alexander; Robinson, David; Carey, Joe V.; Brough, Steve; Woodward, Simon (American Chemical Society, 2017)
ReactIR studies of mixtures of AlEt3 (A) and cyclohex-2-en-1-one (CX) in Et2O indicate immediate formation of the Lewis acid-base complex (CX.A) at -40 oC (K = 12.0 M-1, ΔGoreact -1.1 kcal mol-1). Copper(I) catalysts, derived from pre-catalytic Cu(OAc)2 (up to 5 mol-%) and (R,S,S)-P(binaphtholate){N(CHMePh)2} [Feringa’s ligand (L), up to 5 mol-%] convert CX.A (0.04-0.3 M) into its 1,4-addition product enolate (E) within 2000 sec at -40 oC. Kinetic studies (ReactIR and chiral GC) of CX.A, CX and (R)-3-ethylcyclohexanone (P, the H+ quench product of enolate E) show that the true catalyst is formed in the first 300 sec and this subsequently provides P in 82% ee. This true catalyst converts CX.A to E with a rate law [Cu]1.5[L]0.66[CX.A]1 when [L]/[Cu] ≤ 3.5. Above this ligand ratio inhibition by added ligand with order [L]-2.5 is observed. A rate determining step (rds) of Cu3L2(CX.A)2 stoichiometry is shown to be most consistent with the rate law. The presence of the enolate in the active catalyst (Graphical Abstract) best accounts for the reaction’s induction period and molecularity as [E] ≡ [CX.A]. Catalysis proceeds through a ‘shuttling mechanism’ between two C2 symmetry related ground state intermediates. Each turnover consumes one equivalent of CX.A, expels one molecule of E and forms the new Cu-Et bond needed for the next cycle (Graphic Abstract). The observed ligand (L) inhibition and a non-linear ligand Lee effect on the ee of P are all well simulated by the kinetic model. DFT studies [ωB97X-D/SRSC] support coordination of CX.A to the groundstate Cu-trimer and its rapid conversion to E.